Use of psychotropic substances among elite athletes – a narrative review (Swiss Medical Weekly, 2021)
BACKGROUND AND AIMS Elite athletes may use psychotropic substances for recreational reasons, (perceived) performance enhancement or self-medication. Causes can overlap. For athletes, substance use may be associated with various medical and social risks. Psychoactive substances include alcohol and nicotine, illicit and various prescription drugs, which all have a potential for abuse and dependence. This paper reviews the existing literature on the use of psychoactive substances and associated substance use disorders among elite athletes in terms of prevalence, patterns of use, as well as underlying causes and risk factors. METHODS Due to the heterogeneous and partially fragmentary study data, a narrative approach with selection of applicable publications of a Medline search was chosen. RESULTS The most commonly used psychoactive substances among elite athletes were alcohol, nicotine, cannabis, stimulants and (prescription) opioids. Overall consumption rates are lower in professional sports than in the general population, but use of several substances (smokeless tobacco products, prescription opioids, stimulants) have high prevalence in specific sports and athlete groups. Substance use is subject to multiple risk factors and varies by substance class, sport discipline, country and gender, among other factors. CONCLUSION Knowledge on the underlying causes and patterns of substance use, as well as the prevalence of substance use disorders in professional sports, is still limited. High prevalence of various substances (i.e., nicotine, prescription opioids) may indicate potentially harmful patterns of use, requiring further research. Specific preventive and therapeutic concepts for the treatment of substance use disorders in elite athletes should be developed.